2019
DOI: 10.1109/tr.2019.2897322
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Estimation of Stochastic Flow Network Reliability

Abstract: The Creation Process is an algorithm that transforms a static network model into a dynamic one. It is the basis of different variance reduction methods designed to make efficient reliability estimations on highly reliable networks in which links can only assume two possible values, operational or failed. In this article the Creation Process is extended to let it operate on network models in which links can assume more than two values. The proposed algorithm, called here Multi-Level Creation Process, is the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…A mapping {0, 1} → where is the field of real numbers, i.e. ( ) is an assignment of a real number for each of the possible 2 values of [4,21,12,20,[22][23][24][25][26][27][28].…”
Section: Pseudo-boolean (Switching) Function C(x)mentioning
confidence: 99%
See 3 more Smart Citations
“…A mapping {0, 1} → where is the field of real numbers, i.e. ( ) is an assignment of a real number for each of the possible 2 values of [4,21,12,20,[22][23][24][25][26][27][28].…”
Section: Pseudo-boolean (Switching) Function C(x)mentioning
confidence: 99%
“…This example illustrates an alternative way of applying Test 3 to (11) & (12). Initially branch 2 alone is taken as a keystone element.…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Aggarwal [19], Trstensky and Bowron [20], Ramírez and Gebre [21], Yeh [22], Patra and Misra [23], Fusheng [24], El Khadiri and Yeh [25], Kabadurmus and Smith [26] and Cancela, et al [27] suggested methods for defining a composite performance index related to any network, that integrates the two aforementioned connectivity and capacity aspects. Moreover, Lin et al [28,29] presented an algorithm for evaluation of capacitated flow network in terms of minimal path sets or minimal cut-sets.…”
Section: Introductionmentioning
confidence: 99%